Plant-derived soybean peroxidase stimulates osteoblast collagen biosynthesis, matrix mineralization, and accelerates bone regeneration in a sheep model - Barker, Alexandra J.; Arthur, Agnes; DeNichilo, Mark O.; Panagopoulos, Romana; Gronthos, Stan; Anderson, Peter J.; Zannettino, Andrew C.W.; Evdokiou, Andreas; Panagopoulos, Vasilios (Bone Reports, 2021)
Bone defects arising from fractures or disease represent a significant problem for surgeons to manage and are a substantial economic burden on the healthcare economy. Recent advances in the development of biomaterial substitutes provides an attractive alternative to the current “gold standard” autologous bone grafting. Despite on-going research, we are yet to identify cost effective biocompatible, osteo-inductive factors that stimulate controlled, accelerated bone regeneration.We have recently reported that enzymes with peroxidase activity possess previously unrecognised roles in extracellular matrix biosynthesis, angiogenesis and osteoclastogenesis, which are essential processes in bone remodelling and repair. Here, we report for the first time, that plant-derived soybean peroxidase (SBP) possesses pro-osteogenic ability by promoting collagen I biosynthesis and matrix mineralization of human osteoblasts in vitro. Mechanistically, SBP regulates osteogenic genes responsible for inflammation, extracellular matrix remodelling and ossification, which are necessary for normal bone healing. Furthermore, SBP was shown to have osteo-inductive properties, that when combined with commercially available biphasic calcium phosphate (BCP) granules can accelerate bone repair in a critical size long bone defect ovine model. Micro-CT analysis showed that SBP when combined with commercially available biphasic calcium phosphate (BCP) granules significantly increased bone formation within the defects as early as 4 weeks compared to BCP alone. Histomorphometric assessment demonstrated accelerated bone formation prominent at the defect margins and surrounding individual BCP granules, with evidence of intramembranous ossification. These results highlight the capacity of SBP to be an effective regulator of osteoblastic function and may be beneficial as a new and cost effective osteo-inductive agent to accelerate repair of large bone defects.